2016
DOI: 10.1136/bmj.i245
|View full text |Cite
|
Sign up to set email alerts
|

Effect of structured physical activity on prevention of serious fall injuries in adults aged 70-89: randomized clinical trial (LIFE Study)

Abstract: ABSTRACTinterventiOns A permuted block algorithm stratified by field center and sex was used to allocate interventions. Participants were randomized to a structured, moderate intensity physical activity program (n=818) conducted in a center (twice a week) and at home (3-4 times a week) that included aerobic, strength, flexibility, and balance training activities, or to a health education program (n=817) consisting of workshops on topics relevant to older people and upper extremity stretching exercises. Main Ou… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
96
0
11

Year Published

2016
2016
2020
2020

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 83 publications
(109 citation statements)
references
References 26 publications
2
96
0
11
Order By: Relevance
“…Gait, muscle strength, coordination and reaction velocity can be different depending on the degree of physical activity. Although the harmony of these elements can affect injury severity, we did not investigate these factors . Furthermore, some previous studies have shown that underlying disease and medicine are associated with the prognosis of fall injury .…”
Section: Discussionmentioning
confidence: 99%
“…Gait, muscle strength, coordination and reaction velocity can be different depending on the degree of physical activity. Although the harmony of these elements can affect injury severity, we did not investigate these factors . Furthermore, some previous studies have shown that underlying disease and medicine are associated with the prognosis of fall injury .…”
Section: Discussionmentioning
confidence: 99%
“…Valores muitos elevados, expressos por uma hipermobilidade, podem estar associados a uma maior predisposição a lesões musculares, tendíneas e articulares e a algumas outras doenças específicas do tecido conjuntivo ou a determinadas enfermidades clínicas 29 . Por outro lado, quando presente em valores reduzidos pode representar um risco maior de quedas nos idosos 14 , diminuindo assim a qualidade de vida dos mesmos e prejudicando a execução de atividades rotineiras, tal como sentar e levantar do solo 30 . Dessa forma, os resultados deste estudo sugerem que, em relação à flexibilidade corporal de adultos, parece ser conveniente a inclusão desse tipo de exercício nos programas de exercício físico para que possa ser otimizado esse componente não-aeróbico da aptidão física, aparentemente, independente do histórico de sua prática na juventude.…”
Section: Discussionunclassified
“…A flexibilidade corporal, um dos componentes não-aeróbicos da aptidão física, pode ser definida como a amplitude máxima passiva fisiológica de um dado movimento articular 9 e tende a diminuir com a idade em indivíduos dos dois sexos 10,11 . Diversos estudos têm indicado que uma baixa flexibilidade está associada à uma menor qualidade de vida 12 e a um risco mais alto de quedas em indivíduos mais velhos 13,14 . Embora seja plausível supor que o sedentarismo possa ser acompanhado de níveis menores de flexibilidade corporal é desconhecido se ter sido fisicamente ativo nos primeiros anos de vida poderia contribuir, minimizar ou eliminar essa tendência à redução com o envelhecimento.…”
Section: Introductionunclassified
“…45 In subgroup analyses the authors observed that the hazard ratio for time to first serious fall injury did not differ significantly according to sex (interaction p = 0.14); however, a clinically meaningful qualitative difference was observed with a hazard ratio of 0.62 (95% CI 0.34 to 1.12) in men and of 1.05 (95% CI 0.72 to 1.52) in women. In an analysis that was not prespecified, we repeated the primary analysis in the subgroups of males and females and found similar treatment effects in each (men: IRR 0.87, 95% CI 0.64 to 1.17; women: 0.86, 95% CI 0.68 to 1.09).…”
Section: Post Hoc Analysismentioning
confidence: 93%